The Influence of Campus Facilities, Learning Motivation, and Learning Environment on Student Discipline at Universitas Ekasakti Padang: A Study of Management Students at the Faculty of Economics - Silvia Preity Shinta; Susy Yuliastanty; Delvianti Delvianti; Sigit Sanjaya; Siti Aisyah Rosli (UPI YPTK Journal of Business and Economics, 2026)
Student discipline is an important factor in supporting the effectiveness of the learning process and achieving academic outcomes in higher education. This study aims to examine the effect of campus facilities, learning motivation, and learning environment on student discipline at Universitas Ekasakti Padang. The study focuses on students of the Management Study Program, Faculty of Economics. This research employed a quantitative approach with data collected through questionnaires distributed to 57 respondents selected using purposive sampling. The data were analyzed using Partial Least Squares (PLS) to examine the relationships between campus facilities, learning motivation, learning environment, and student discipline. The results of the study show that campus facilities have a positive and significant effect on student discipline, learning motivation has a positive and significant effect on student discipline, and learning environment has a positive and significant effect on student discipline. Furthermore, campus facilities, learning motivation, and learning environment simultaneously contribute to student discipline. These findings indicate that adequate campus facilities, strong learning motivation, and a supportive learning environment are important factors in encouraging students to maintain discipline in their academic activities. The study provides practical implications for university management to improve campus facilities, strengthen students' learning motivation, and create a conducive learning environment to support student discipline.